2021
DOI: 10.1177/1179556521992354
|View full text |Cite
|
Sign up to set email alerts
|

New PAX2 Mutation Associated with Polycystic Kidney Disease: A Case Report

Abstract: Background: Congenital anomalies of the kidney and urinary tract (CAKUT) are the leading cause of end stage renal disease in children. Diagnosis by genetic testing has proven challenging due to its genetic and phenotypic heterogeneity, as well as incomplete penetrance. We report a case on a 16-months old female with a history of renal cysts and a PAX2 mutation. Case presentation: The patient presented with a prenatal diagnosis of Potter sequence and a postnatal diagnosis of renal cysts. An ultrasound at 20 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Hsa-mir-21-5p [576] and PAX2 [577] are believed to be associated with FSGS. Liu et al [578], Park et al [579], Yang et al [580], Yu et al [581] and Forero-Delgadillo et al [582] mentioned that hsa-mir-21-5p, STAT3, STAT1, GATA2 and PAX2 were related to other kidney diseases. Studies have indicated that hsa-mir-21-5p [583], STAT3 [584], STAT1 [585] and GATA2 [586] plays a substantial role in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Hsa-mir-21-5p [576] and PAX2 [577] are believed to be associated with FSGS. Liu et al [578], Park et al [579], Yang et al [580], Yu et al [581] and Forero-Delgadillo et al [582] mentioned that hsa-mir-21-5p, STAT3, STAT1, GATA2 and PAX2 were related to other kidney diseases. Studies have indicated that hsa-mir-21-5p [583], STAT3 [584], STAT1 [585] and GATA2 [586] plays a substantial role in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Se manifiesta con hipo/displasia renal y displasia o coloboma del nervio óptico principalmente. También se puede presentar hipoacusia neurosensorial bilateral e hiperlaxitud articular y de la piel 14,15 .…”
Section: Anomalías Congénitas Del Riñón Y Tracto Urinario (Cakut)unclassified
“…Until 2021, 92% of the PAX2 mutations that had been described had kidney dysfunction of varied degrees, 77% presented colobomas or ocular dysplasia and 7% had hearing loss [ 34 , 35 ].…”
Section: Pax2 Gene and Kidneysmentioning
confidence: 99%
“…A PAX2 mutation was identified in a patient with a prenatal diagnosis of the Potter sequence, and a postnatal ultrasound revealed renal cysts [ 34 ]. The variant found in this case was not found in either of the patient’s parents, so it was considered a de novo mutation.…”
Section: Pax2 Gene and Kidneysmentioning
confidence: 99%
See 1 more Smart Citation